Failure analysis using X-ray computed tomography of composite sandwich panels subjected to full-scale blast loading. (15th November 2017) - Rolfe, Emily; Kelly, Mark; Arora, Hari; Hooper, Paul A.; Dear, John P.
Abstract: The tailorable mechanical properties and high strength-to-weight ratios of composite sandwich panels make them of interest to the commercial marine and naval sector, however, further investigation into their blast resilience is required. The experiments performed in this study aimed to identify whether alterations to the composite skins or core of a sandwich panel can yield improved blast resilience both in air and underwater. Underwater blast loads using 1.28 kg TNT equivalent charge at a stand-off distance of 1 m were performed on four different composite sandwich panels. Results revealed that implementing a stepwise graded density foam core, with increasing density away from the blast, reduces the deflection of the panel and damage sustained. Furthermore, the skin material affects the extent of panel deflection and damage, the lower strain to failure of carbon-fibre reinforced polymer (CFRP) skins reduces deflection but increases skin debonding. A further two panels were subjected to a 100 kg TNT air blast loading at a 15 m stand-off to compare the effect of a graded density core and the results support the underwater blast results. Future modelling of these experiments will aid the design process and should aim to include material damage mechanisms to identify the most suitable skins.